Tilting the Supply Schedule to Enhance Competition in Uniform-Price Auctions - Marco LiCalzi; Alessandro Pavan (Fondazione Eni Enrico Mattei (FEEM), 2003)
Uniform-price auctions of a divisible good in fixed supply admit underpricing equilibria, where bidders submit high inframarginal bids to prevent competition on prices. The seller can obstruct this behavior by tilting her supply schedule and making the amount of divisible good on offer change endogenously with its (uniform) price. Precommitting to an increasing supply curve is a strategic instrument to reward aggressive bidding and enhance expected revenue. A fixed supply may not be optimal even when accounting for the cost to the seller of issuing a quantity different from her target supply.
Keywords: D44; E58; 330; Uniform-price auction; divisible good; strategic role of the seller; endogenous supply; Treasury and IPO auctions; Auktionstheorie; Preis; Wettbewerb; Theorie